Influence of suspension heating rate on properties of zeolite 13X: Original scientific paper - Janković, Mladen; Perušić, Mitar; Damjanović, Vladimir; Filipović, Radislav; Obrenović, Zoran; Tadić, Goran; Kostić, Duško (HEMIJSKA INDUSTRIJA (Chemical Industry), 2023)
It is known that the temperature of crystallization during the synthesis of zeolite is one of the most important process parameters. However, during the research work on the synthesis of zeolite 13X and the introduction of this material into regular industrial production, it was noticed that the heating rate of the starting reaction suspension can have an equally important influence. This influence can be so pronounced that a difference of just a few minutes in reaching the crystallization temperature can make a significant difference in product quality, affect the presence of other phases in the crystal, or even determine the direction of zeolite crystallization. Therefore, the aim of this work was to show the influence of the heating rate on the quality of the obtained 13X zeolite powders. The obtained samples were analysed in terms of crystallinity (by X-ray diffraction), chemical composition, granulometry and specific surface area (by Brunauer-Emmett-Teller analysis), and regarding water and CO2 adsorption capacities. Additionally, scanning electron microscopy analysis of the samples showed the morphological characteristics of different 13X zeolite powders. The analysis results of the obtained powders confirmed the influence of the heating rate and helped to define the optimal synthesis parameters i.e. the initial temperature and heating time, that resulted in stable product quality.